A years work in the college nursery - Gingery, Clark A. (My University, 1902)
Introduction: In “A Year’s Work in the College Nursery” no chronological arrangement shall be attempted; but a simple statement of the work usually done in the College nursery during an “ordinary year” will be given, and the time for doing the various kinds of work will in most cases be incidentally stated. Collecting Seeds—Seeds for the nursery are collected as soon as convenient after ripening; there is more or less risk in leaving most kinds of seeds after they have ripened: seed receptacles burst allowing the seeds to drop out, birds ravage some of the fleshy fruits, and nuts are carried away by other collectors and by squirrels. No method or methods of gathering need be detailed as the best method for the case in hand usually suggests itself at the opportune time.
Citation: Gingery, Clark A. A years work in the college nursery. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Horticulture; Kansas State Agricultural College; Nursery; Theses; Manuscripts (documents)